Can the University Save Europe? - Jo Ritzen (Institute for the Study of Labor (IZA), 2012)
Higher education is in the position to save Europe by rendering a substantial contribution to sustainable economic growth. For that purpose higher education must strengthen its innovative power in entrepreneurship education and by focusing research more on societal problems, while being better empowered and enabled by Governments. Universities must show leadership in resolving or channeling the major societal questions. More European competition between universities in education and research would be helpful. Universities can contribute to recreating hope and optimism through more innovation in the economy.
Keywords: D31; F55; I22; I23; I24; I25; I28; J24; O31; O47; O52; 330; hope; attitudes; Europe; economic growth; higher education; labor market; innovation; competition; Hochschule; Innovation; Wirtschaftswachstum; Wettbewerb; Europa